Evaluating Arundo donax efficiency for pharmaceutical compounds removal from synthetic wastewater in horizontal flow constructed wetland - Mumtaj, Zeba Ali; Khan, Saimah; Ahmad, Nafees; Khan, Abdul Rahman; Alkahtani, Meshel Qablan; Morabet, Rachida El (Scientific reports, 2025)
Constructed wetlands use vegetation as a natural medium to filter out pollutants from wastewater. It is simple to use, low maintenance, low running costs, sustainable, and eco-friendly. This has led to numerous studies to evaluate its performance in treating pollutants, including pharmaceutical compounds, ranging from conventional to emerging contaminants. However, there is still a lack of work on removal efficiency of pharmaceutical compounds individually assessed with conventional parameters removal. In this study, two horizontal flow constructed wetlands were fabricated; one constructed wetland was made with plants and other without plant. The pharmaceuticals used for this study are Levofloxacin, Amoxicillin , Ketorolac, Fluconazole and Aspirin. The water samples were collected as grab samples after 24 h of duration. The conventional and non-conventional parameters were studied for influent and effluent wastewater. From the results, it was found that significant removal efficiencies were observed in all parameters. The removal efficiency of above pharmaceuticals in PCW follows the order Fluconazole (98%) > Aspirin (98%) > Levofloxacin (98%) > Ketorolac (88%) > Amoxicillin (52.18%). The removal efficiency of above pharmaceuticals in UPCW follows the order Fluconazole (92%) > Ketorolac (87%) > Aspirin (79%) > Levofloxacin (71%) > Amoxicillin (35%). It was also concluded from the results that the PCW (up to 98%) provide higher removal efficiency as compare to UPCW (up to 90%). Further research may concentrate on assessing alternative procedures in conjunction with CWs development.